Feasibility and performance of the Idylla™ NRAS/BRAF cartridge mutation assay on thyroid liquid‐based fine‐needle aspiration. Issue 12 (26th October 2021) - Hamadou, Maud; Lopez, Jonathan; Benzerdjeb, Nazim; Cugnet‐Anceau, Christine; Schnoering, Gwenaelle; Besançon, Julie; Mezrag, Saliha; Lapras, Veronique; Denier, Marie‐Laure; Descotes, Françoise; Decaussin‐Petrucci, Myriam
Abstract: Background: Thyroid nodules with indeterminate cytology represent up to 30% of cases. Molecular testing is now highly recommended to improve management. This study aimed to evaluate the use of the Idylla™ NRAS / BRAF mutation test, a rapid and automated polymerase chain reaction (PCR) assay validated for fixed paraffin‐embedded use, on residual thyroid liquid‐based fine‐needle aspiration (LB‐FNA). Methods: Concordance between mutations detected by the Idylla™ assay and the gold‐standard qPCR was assessed by splitting in two aliquots 31 BRAF or RAS mutated and 5 non‐mutated LB‐FNA samples. Samples were obtained either from simulated FNA after thyroidectomy or from FNA obtained during routine care. A third aliquot was used to assess the limit of detection of Idylla™ for five mutated samples. Results: The Idylla™ assay showed a sensitivity of 97% and a specificity of 83% as results were concordant for 34 out of 36 samples. One discordant sample concerned a BRAF p.K601E‐mutation which is not detected by the Idylla™ cartridge. The other showed a false‐positive NRAS p.A146T detection and a weak BRAF p.V600E detection. The limit of detection of the Idylla™ assay was not reached by the dilution assay. Conclusion: Idylla™ NRAS / BRAF mutation testing can be performed on residual thyroid LB‐FNA, using low DNA quantity input, thus not requiring a dedicated sample. The Idylla™ NRAS / BRAF assay offers a quick and easy first step for analyzing the main molecular alterations in indeterminate thyroid nodules, hence improving diagnostic management.